2011
DOI: 10.1007/s12013-011-9230-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on the Prevention of Post-ERCP Pancreatitis by Pancreatic Duct Stenting

Abstract: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is one of the most common and serious complications of ERCP, which has become a major concern for digestive endoscopists. In the present study, we examine whether pancreatic duct stenting can reduce the incidence of PEP. Forty patients who underwent an ERCP in our hospital were selected according to their risk factors for PEP. They were randomly divided into two groups: (1) 20 subjects received a pancreatic duct stenting after ERCP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…In addition, the placement of the ENPD catheter into the caudal pancreatic duct, even with IDUS and brushing of the pancreatic duct may inhibit PEP. For the prevention of PEP, the usefulness of an endoscopic pancreatic duct stent (EPS) has been reported . These reports showed that placement of the EPS contributes to the reduction of PEP in high‐risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the placement of the ENPD catheter into the caudal pancreatic duct, even with IDUS and brushing of the pancreatic duct may inhibit PEP. For the prevention of PEP, the usefulness of an endoscopic pancreatic duct stent (EPS) has been reported . These reports showed that placement of the EPS contributes to the reduction of PEP in high‐risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because the incidence of PEP associated with ENPD catheter placement has not been reported, it was inferred. A randomized comparative study on placement of a pancreatic stent for the purpose of prevention of PEP showed that the rate of PEP after placement was 0–20% . It was assumed that the rate of PEP with a 5‐Fr ENPD catheter was 13%, and the rate of PEP with a 4‐Fr ENPD catheter was 3%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that it is important to avoid unnecessary pancreatograms when performing SEMS placements for distal MBO. Prophylactic placement of pancreatic duct stent might decrease the risk of pancreatitis after SEMS placement especially for patients with non‐pancreatic cancer because its efficacy at preventing post‐ERCP pancreatitis in high‐risk patients has been established in several randomized controlled trials …”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs have demonstrated the efficacy of PS placement (Table 1). 29,30,31,32,33,34,35,36,37,38,39,40,41,42 Moreover, several meta-analyses have demonstrated its effect on PEP risk reduction compared with non-PS placement 43,44,45,46. In a recent meta-analysis that included six additional RCTs that were published since 2010, the incidence of PEP decreased from 19% in the control group to 7% 47.…”
Section: Specific Endoscopic Techniquesmentioning
confidence: 99%